Study of the optimization model for traffic flow. (October 2019) - Yun-xiang, Han; Jian-wei, Zhang; Xiao-qiong, Huang
Highlights: This paper proposes a modeling framework adapted to the analysis of air traffic flows. The problems of system balance analysis can be posed as the control of queues. The techniques can ensure that the queues are uniformly distributed. Abstract: The imbalance may lead to an adverse effect over the airspace network for scheduled air traffic system, which is a major concern to air traffic controller. This paper focuses on the problems related to coordinating departure flight within the airspace network to meet the constraints so as to produce regular traffic flow. Particularly, we propose a method to generate regular flights on the basis of max-plus model. Firstly, the system model is built. Then, a regular schedule is obtained based on the optimization algorithm. In this way, the control method can be derived for the air transportation network by incorporating system parameters and traffic flow data, The air traffic flow control policy has the potential to be applied to large-scale airspace networks in real-time operations.